2003
DOI: 10.1002/ptr.1052
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic effect of Opuntia lindheimeri Englem. in a diabetic pig model

Abstract: The hypoglycaemic activity of Opuntia lindheimeri Englem. was investigated in non-diabetic (control pigs) and streptozotocin-induced diabetic pigs using an enteral (oral) route of administration. Following the administration of O. lindheimeri extract (0, 250 or 500 mg/kg body weight), blood glucose concentrations in control pigs fluctuated around initial baseline concentrations, but were not consistently affected by either the dose of O. lindheimeri or by the time following administration. In contrast, adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…In feeding trials with pigs, diabetic individuals exhibited reduced blood glucose levels 1 h after ingestion of an extract from O. lindheimeri Engelm. When 250 mg extract per kg body weight were applied, a 24% glucose decline was registered while at a 500 mg dose, even a reduction by 42% was noted [163]. Since diabetic pigs develop the same secondary injuries as humans such as microvascular eye and kidney damage as well as proliferating nonresponsiveness to insulin, this model should be preferred to tests on dogs, rabbits, rats, or mice.…”
Section: Hypoglycemic and Antidiabetic Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…In feeding trials with pigs, diabetic individuals exhibited reduced blood glucose levels 1 h after ingestion of an extract from O. lindheimeri Engelm. When 250 mg extract per kg body weight were applied, a 24% glucose decline was registered while at a 500 mg dose, even a reduction by 42% was noted [163]. Since diabetic pigs develop the same secondary injuries as humans such as microvascular eye and kidney damage as well as proliferating nonresponsiveness to insulin, this model should be preferred to tests on dogs, rabbits, rats, or mice.…”
Section: Hypoglycemic and Antidiabetic Effectmentioning
confidence: 96%
“…Since diabetic pigs develop the same secondary injuries as humans such as microvascular eye and kidney damage as well as proliferating nonresponsiveness to insulin, this model should be preferred to tests on dogs, rabbits, rats, or mice. While neither the active component nor the underlying mechanism could be elucidated, it was suspected that a protein-like compound similar to insulin was responsible for the effects observed [163]. Based on a two-month study with regular consumption of O. fuliginosa Griffiths extract, a daily intake of 1 mg per kg body weight was recommended [164].…”
Section: Hypoglycemic and Antidiabetic Effectmentioning
confidence: 98%
“…In the present study, we examined the antiviral activity of the cactus Opuntia ficus indica, and attempted to extract, isolate and identify the active compound(s). This plant, which grows in harsh climatic conditions (heat and dryness), was described as exhibiting several medicinal virtues including anti-diabetic [2,3], anti-cholesterol [4,5], anti-inflammatory [6], antioxidant [7], and anti-tumor [8] properties. However, reports on the antiviral activity of this cactus are limited to one publication [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in healthy volunteers and type 2 diabetes mellitus patients demonstrated that the broiled stems of Opuntia possess hypoglycemic activity (Frati‐Munari et al ., 1990, 1987; Meckes‐Lozyoa and Roman‐Ramos, 1986). Moreover, the hypoglycemic effects of Opuntia extracts have been confirmed in several animal models of diabetes (Ibanez‐Camacho et al ., 1983; Laurenz et al ., 2003). The majority of the mentioned studies on the antidiabetic potential of Opuntia extracts focused on O. streptacantha (Alarcon‐Aguilar et al ., 2003; Frati‐Munari et al ., 1988; Frati et al ., 1990; Ibanez‐Camacho and Meckes‐Lozoya, 1983; Ibanez‐Camacho et al ., 1983; Meckes‐Lozoya and Ibanez‐Camacho, 1989).…”
Section: Introductionmentioning
confidence: 99%